2023
DOI: 10.1111/jce.15939
|View full text |Cite
|
Sign up to set email alerts
|

Sotalol in neonates for arrhythmias: Dosing, safety, and efficacy

Abstract: Introduction Various agents may be utilized to manage supraventricular tachycardia (SVT) in neonates and infants. Recently, sotalol has piqued interest given its reported success in managing neonates and infants with SVTs, especially with the intravenous formulation. While the manufacturer recommends using an age‐related nomogram in neonates and young infants to guide doses, clinical reports describe various dosing based on weight (mg/kg) or on body surface area (BSA) in mg/m2. Given the reported variation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…73 Nonetheless, several studies have reported that sotalol doses substantially higher than those recommended by the nomogram are safe and effective for neonates and infants with refractory supraventricular arrhythmias. 56,74…”
Section: Sotalolmentioning
confidence: 99%
“…73 Nonetheless, several studies have reported that sotalol doses substantially higher than those recommended by the nomogram are safe and effective for neonates and infants with refractory supraventricular arrhythmias. 56,74…”
Section: Sotalolmentioning
confidence: 99%